Comparative Cytotoxicity of Selected Mikania species using Brine Shrimp Lethality Bioassay and Sulforhodamine B (SRB) Assay (Bangladesh Pharmaceutical Journal, 2021)
This study aims to assess the comparative cytotoxic activity of the ethanolic extract of Mikania cordata (MC), Mikania micrantha (MM) and Mikania scandens (MS) (Family: Asteraceae) using brine shrimp lethality bioassay and colorimetric sulforhodamine B assay method. In SRB assay, A549 human lung carcinoma, SK-Mel-2 skin melanoma and B16F1 mouse melanoma cell lines were used. In brine shrimp assay, the LC50 for MC, MM, MS and vincristine were found to be 29.04, 15.84, 32.35, and 1.2 μg/ml, respectively. The results indicate that all the Mikania species showed moderate lethality against nauplii. In SRB assay, 50% cell growth inhibition concentration (IC50) of MC, MM, MS and cisplatin against B16-F1 were 33, 15, 39 and 6.8 μg/ml, respectively. Similar data were observed for other cell lines indicating moderate cytotoxicity of the extracts. Among the species, M. micrantha showed relatively potent cytotoxic effect followed by M. cordata and M. scandens. Similar data were observed for brine shrimp lethality bioassay and the results suggest that M. micrantha possesses highest cytotoxic potentials among all the species.Bangladesh Pharmaceutical Journal 24(1): 11-16, 2021